Effects of different types of biochar on the anaerobic digestion of chicken manure. (March 2019) - Pan, Junting; Ma, Junyi; Liu, Xiaoxia; Zhai, Limei; Ouyang, Xihui; Liu, Hongbin
Highlights: The fruitwood biochar could enhance methane production substantially. The transformation of substances was accelerated by biochar. The buffering capacity of anaerobic digestion system was enhanced by biochar. Abstract: This study investigated the impact of different types of biochar on the anaerobic digestion (AD) of chicken manure. Wheat straw, discarded fruitwood, and air-dried chicken manure were pyrolysed at 350, 450, and 550 °C to generate biochar. A lab-scale batch anaerobic digestion experiment was conducted at 35 ± 1 °C. Substantial improvements in methane production were observed for all nine types of biochar. With the production of 294 mL CH4 /g VSadded, fruitwood char pyrolysed at 550 °C increased the methane yield by 69% from the control. Characteristic analysis indicated that fruitwood char pyrolysed at 550 °C exhibited the largest specific surface area and highest total ammonia nitrogen reduction capacity. The buffering capacity of the AD system was improved by the biochar through accelerating the transformation of macromolecular substances to dissolved substrates and reducing the contents of soluble salts, total ammonia nitrogen, and free ammonia.